Faktor Risiko Kejadian Carpal Tunnel Syndrome (CTS) pada Wanita Pemetik Melati di Desa Karangcengis, Purbalingga - Kurniawan, Bina; Jayanti, Siswi; Setyaningsih, Yuliani (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2008)
Background: Carpal Tunnel Syndrome (CTS) is one of work related disease that would be a big problem in industrial health. CTS are related to some factors including Individual, work, and health. About 60% jasmine pluckier in Karangcengis Village show some symptoms of CTS such as painful, numbness, and cramps. CTS case was determined based on NIOSH criteria including the symptoms of CTS, physical diagnosis by phalen test, and the historical occupation. The aim of this research was to show the association between characteristics, repetitive motionfrequency, and health factors with carpal tunnel syndrome among jasmine pluckier in Karangcengis Village, Purbalingga.Method: This research was an explanatory research using cross sectional approach. Sample of this research was the jasmine pluckier comprise of 72 workers selected by non probability convenience sample (accidental sample) method.Result: Statistics test using chi-square test (Ã¡ =0,05) showed that age (p=1,000), duration of work (p=0,913), years of work (p=0,187), and health factors (p=0,083) had no relation to CTS, but repetitive motion frequency (p=0,013) had relationship with CTS.Keywords: CTS, risk factors, jasmine pluckier.